Strengthening Malaria Service Delivery through Supportive Supervision and Community Mobilization in an Endemic Indian Setting : An Evaluation of Nested Delivery Models - Das, Ashis; Friedman, Jed; Kandpal, Eeshani; Ramana, GNV; Das Gupta, R K; Pradhan, Madan M; Govindaraj, Ramesh (World Bank, Washington, DC, 2014)
Malaria continues to be a prominent global public health challenge, in part because of the slow population adoption of recommended preventive and curative behaviors. This paper tests the effectiveness of two service delivery models designed to promote recommended behaviors, including prompt treatment seeking for febrile illness, in Odisha India. The tested modules include supportive supervision of community health workers and community mobilization promoting appropriate health seeking. Program effects were identified through a randomized cluster trial comprising 120 villages from two purposively chosen malaria-endemic districts. Significant improvements were measured in the reported utilization of bed nets in both intervention arms vis-à-vis the control. Although overall rates of treatment seeking were equal across the study arms, treatment seeking from community health workers was higher in both intervention arms and care seeking from trained providers also increased with a substitution away from untrained providers. Further, fever cases in both treatments were more likely to have received timely medical treatment (within 24 hours) from a skilled provider. The study arm with supportive supervision was particularly effective in shifting care seeking to community health workers and ensuring prompt diagnosis and treatment. A community-based intervention combining the supportive supervision of community health workers with intensive community mobilization can be effective in shifting care seeking and increasing preventive behavior, and thus may be used to strengthen the national malaria control program.